S100P as a Marker for Urothelial Histogenesis: A Critical Review and Comparison With Novel and Traditional Urothelial Immunohistochemical Markers. (May 2017) - Suryavanshi, Moushumi; Sanz-Ortega, Julian; Sirohi, Deepika; Divatia, Mukul K.; Ohe, Chisato; Zampini, Claudia; Luthringer, Daniel; Smith, Steven C.; Amin, Mahul B.
Abstract : S100P, or placental S100, is a member of a large family of S100 proteins and considered to be a promising immunohistochemical marker to support urothelial differentiation. This review synthesizes published data regarding the expression of S100P in urothelial carcinoma across histological grade and variant patterns, and in other malignancies, in an effort to summarize the state of understanding of this marker and evaluate its potential. We provide also a broad comparison of S100P with other contemporary and traditional urothelial markers and outline the potential utility of S100P in various diagnostically challenging scenarios. Taken in context, we recommend that to provide immunohistochemical support for consideration of urothelial differentiation, S100P may be included in a panel of markers (due to its high sensitivity), with better established (GATA3) and more specific (uroplakin 2) markers, for comparison with corresponding markers of other primary sites under consideration, depending on the clinical context. We emphasize that the overall most appropriate panel for any given case depends on the differential diagnosis engendered by the morphology encountered, and the constellation of clinical findings. As always with immunohistochemical panels, expected positive and negative markers for each diagnostic consideration should be included. Finally, since as of date there are no optimally sensitive or specific markers of urothelial differentiation, all final diagnoses relying on immunohistochemical support should be made in the appropriate clinical and histological context.